Efeitos da incorporação de resíduos de espuma rígida de poliuretano em compostos poliméricos a base de polipropileno - Pereira, Simone Fontana (2012)
This research fits in the technological development area and is aimed to evaluate the effects of adding waste of rigid polyurethane foam in the polymeric compounds based on polypropylene. The results of this research will certainly contribute to finding a solution to the large volume of industrial wastes of rigid polyurethane foam that arise from the waste process of handling thermal insulation from the production of refrigerators and freezers. The analysis of the effects of adding scraps of rigid foam in polypropylene copolymer was made by evaluating the physical, mechanical and thermal properties of the compounds when compared to the behavior of neat polypropylene. Moreover, the technique of Scanning Electron Microscopy was used to observe the microstructure of the final compound. The rigid polyurethane foam, after grinding, was incorporated into polypropylene by blending on the twin extruder and then the granulated materials obtained were injected to obtain the samples. In general, the compounds showed good processability in the experimental phase and looked good as can be seen in the SEM micrographs. The mechanical properties showed that the incorporation of PUR in PP copolymers promoted a brittle behavior in the compounds decreasing the main mechanical properties tested. However, the addition of the compatibilizing agent used, PP-g-MA helped in improving these properties. The use of PUR in polypropylene compounds brought advantages in terms of reducing waste disposal and thus has economic and environmental advantages and also viability in applications where high mechanical strength is not required.